Pharmacogenetic variants of infliximab response in young patients with inflammatory bowel disease. Issue 6 (19th June 2021) - Curci, Debora; Lucafò, Marianna; Cifù, Adriana; Fabris, Martina; Bramuzzo, Matteo; Martelossi, Stefano; Franca, Raffaella; Decorti, Giuliana; Stocco, Gabriele
Abstract: Infliximab is commonly used in inflammatory bowel disease (IBD), however, differences in clinical response among patients are common. Several studies have considered the possibility that these differences are caused by genetic variability even if no unique marker has been yet identified in pediatric patients. We evaluated the impact of two candidate single‐nucleotide polymorphisms (SNPs) rs396991 in FCGR3A and rs1800629 in TNFα genes on infliximab response in an Italian cohort of 76 pediatric patients with IBD. Results showed that patients with the variant FCGR3A allele had a reduced clinical response at the end of induction ( p value = 0.004), at 22 weeks ( p value = 0.001), and at 52 weeks of treatment ( p value = 0.01). A significant association between the FCGR3A variant and median infliximab levels measured during maintenance therapy was also observed: patients with wild type genotype had higher infliximab levels compared to patient with variant allele. Furthermore, patients with the variant allele had a higher probability to produce antidrug antibodies (ADAs). No association was found among the TNFα SNP, clinical response, and infliximab levels. This study addressed for the first time in pediatric patients with IBD, the association of FCGR3A SNP, infliximab response, and ADA production.